Determination of Phenolic and Flavonoid Content of Ethanol Extract of Manila Sawo Leaf (Manilkara zapota L.) from Wajo District by Uv-Vis Spectrophotometry - Suhaenah, Asriani; Hartina, Suki; Aminah, Aminah (Pharmaceutical Reports, 2024)
Sapodilla Manila (Manilkara zapota L.) is a plant that is widely known by the public. People usually use sapodilla leaves as traditional medicine. Efficacy obtained from the presence of phenolic compounds and flavonoids in these plants. This study aims to determine the phenolic and flavonoid content of ethanol extract in sapodilla leaves (Manilkara zapota L.) from Wajo district. This research method used UV-Visible spectrophotometry and the reference standard used were gallic acid (phenolic) and quarcetin (flavonoid). The results showed that the average phenolic content of the ethanol extract of sapodilla leaves at a concentration of 100 ppm was 150.28 mgGAE/g extract and the average flavonoid content of the ethanol extract of sapodilla leaves at a concentration of 300 ppm was 36.577 mgQE/g extract.